2015
DOI: 10.1017/jns.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of coffee polyphenols increases postprandial release of the active glucagon-like peptide-1 (GLP-1(7–36)) amide in C57BL/6J mice

Abstract: The widespread prevalence of diabetes, caused by impaired insulin secretion and insulin resistance, is now a worldwide health problem. Glucagon-like peptide 1 (GLP-1) is a major intestinal hormone that stimulates glucose-induced insulin secretion from β cells. Prolonged activation of the GLP-1 signal has been shown to attenuate diabetes in animals and human subjects. Therefore, GLP-1 secretagogues are attractive targets for the treatment of diabetes. Recent epidemiological studies have reported that an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
0
28
1
2
Order By: Relevance
“…ACCEPTED MANUSCRIPT 20 Our previous study demonstrated that coffee polyphenols increased GLP-1 secretion from enteroendocrine cells and in mice [14]. However, the present study did not observe a significant increase in blood active GLP-1 levels after coffee polyphenol ingestion.…”
Section: Accepted Manuscriptcontrasting
confidence: 90%
See 2 more Smart Citations
“…ACCEPTED MANUSCRIPT 20 Our previous study demonstrated that coffee polyphenols increased GLP-1 secretion from enteroendocrine cells and in mice [14]. However, the present study did not observe a significant increase in blood active GLP-1 levels after coffee polyphenol ingestion.…”
Section: Accepted Manuscriptcontrasting
confidence: 90%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 14 The initial blood parameters in the subjects were similar between the two test beverages (Table 1). The fasting levels of AST were significantly different (P < 0.05) between the beverages (Table 1).…”
Section: Postprandial Blood Parameters and Vascular Responses In Healmentioning
confidence: 85%
See 1 more Smart Citation
“…A 2.5-fold increase in glucose transport was described as an additive action with insulin [44]. Polyphenols in coffee stimulate GLP 1, which is a major intestinal hormone that activates glucose-induced insulin secretion from β-cells [45]. Prolonged activation of the GLP-1 signal has been shown to attenuate diabetes in animals and human subjects.…”
Section: Coffee and Type 2 Diabetesmentioning
confidence: 99%
“…Other reported T2D-related outcomes with coffee compounds include an inhibitory effect of CGAs on glucose uptake in the intestine and stimulation of glucagon-like-peptide 1 (GLP1) secretion from gastrointestinal cells, which in turn can modify gastric emptying and stimulate insulin secretion (Fujii, Osaki, Hase, & Shimotoyodome, 2015;Johnston, Clifford, & Morgan, 2003). However, contradictory results exist regarding the impact on GLP1 and thus indirectly on insulin release (Tunnicliffe, Eller, Reimer, Hittel, & Shearer, 2011).…”
Section: Impact Of Bioactive Coffee Components On Insulin Resistance mentioning
confidence: 99%